Surprise of Meaux in 1567 (engraving) - Creator:Gustave Roux (Wikimedia Commons, 1860)
Notice iconographique issue de Wikimedia Commons. Titre: Surprise of Meaux in 1567 (engraving). Surprise of Meaux in 1567 (engraving)
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons